THE PROBLEM OF ANOMALOUS FILTRATION AND SOLUTE TRANSPORT IN AN INHOMOGENEOUS POROUS MEDIUM - Makhmudov, J; Sulaymonov, F; Usmonov, A; Kuljanov, J (Журнал математики и информатики, 2023)
In this work, filtration and solute transport in a one-dimensional medium of fractal structure is considered.